Penguatan Ekoteologi dan Konstruksi Perlindungan Hak Asasi Lingkungan Berbasis Tafsir Al-Qur'an - Khamdan, Muh; Annibras, Nablur Rahman; Wiharyani, Wiharyani (Jurnal Penelitian Ilmu Ushuluddin, 2024)
This article aims to explain the construction of ecotheology from the perspective of contemporary interpreters based on comparison of contemporary interpretive texts. The creation of humans as caliphs on earth which has the meaning of being a substitute has experienced a shift in meaning in several contemporary interpretations. This theoretical study of environmental issues was studied using descriptive qualitative methods through interpretation results with plural dimensions. The data processing and analysis process is carried out using content analysis methods in thematic interpretation aspects related to environmental issues. A number of terms related to ecology in the Al-Qur'an show the relationship between human rights and environmental rights. Humans are ecologically part of the living environment, so the sustainability of human entities actually depends on environmental balance. The universe has a human right to be treated as well as possible as a life partner for humans to carry out their shared roles in serving God.